Peer Rejection and Academic Performance in Early Childhood: The Mediating Role of Special Educational Needs of Spanish Students - Luis J. Martín-Antón; Paula Molinero-González; Miguel Á. Carbonero-Martín; Wendy L. Arteaga-Cedeño; José Luis Rodríguez-Sáez (MDPI AG, 2024)
Peer rejection occurs at all stages of education, including infant education, and entails serious consequences, both immediately and in the future, in all areas of children's development. This study aims to gain insight into the link between peer rejection and academic performance, mediated by the presence of special educational needs (SEN). The study involved the participation of 758 students (397 male) in the second cycle of early childhood education (3-6 years old) in Spain who were given a sociometric test to ascertain the sociometric distribution of each classroom. Their teachers were asked to record the academic performance of each student in terms of language, logic-mathematics, psychomotor ability, and overall performance. Teachers were also asked to identify whether or not students had SEN. By applying a multivariate variance analysis (MANOVA) that considered the presence or otherwise of peer rejection and the presence or otherwise of SEN as independent variables, results show that rejected students display poorer academic performance in all areas. The same was also found to be true for those with SEN. As a result, rejected students with SEN are seen to exhibit the poorest academic performance and suffer two-fold stigmatisation.